Cemal Halvetî (ö. 899/1494)’nin Etvâr-ı Seb‘a Anlayışının Sûfî Psikolojisi Açısından Tahlili / The Analysis of Jamal Khalwati’s (d. 899/1494) al-Atvar al-Seb’a with Regard to Sufi Psychology - Işıtan, İbrahim (Journal of History Culture and Art Research, 2017)
Abstract The concept of al-Atwar al-Seb’a (seven stages) is an important issue in the Khalwati tradition. Khalwati Sufis evaluates the seven stages of human ego within the spiritual experience they have experienced and have revealed the application of which measures used in self-development phases with different criteria. For this reason, a rich culture of al-Atwar al-Seb’a has been formed in the Khalwati tradition and many pamphlets have been written on this topic. It is important for today’s academic world to deal with these issues within the framework of spiritual psychology. Because a new spiritual psychology tradition has begun to emerge as parallel to modern psychology. By force of the method of modern psychology its perception of self-development is more physio-psychological and this viewpoint neglects the inner/spiritual dimension of man. On the other hand, the self-development model of the Sufi tradition by force of the Islamic belief is psycho-spiritual and accordingly the spiritual development of the human ego exists. In this paper, we will reveal Jamal Khalwati’s thoughts about human ego and its spiritual development in seven stages, and try to show the contribution of them to the development of Sufi psychology. Öz Etvâr-ı seb‘a/yedi evre anlayışı, halvetî gelenekte önemli bir konu olarak ele alınmıştır. Halvetî sûfîler insan beninin yedi aşamasını, yaşadıkları mânevî tecrübe çerçevesinde değerlendirmişler ve farklı kriterlerle benlik gelişimi evrelerinin hangi ölçüler vasıtasıyla yapıldığının uygulamasını ortaya koymuşlardır. Bu nedenle halvetî gelenekte zengin bir etvâr-ı seb‘a kültürü oluşmuş ve bu konuda birçok risale kaleme alınmıştır. Bu risalelerin mânevî psikoloji çerçevesinde ele alınması günümüz akademik dünyası için önem arz etmektedir, çünkü modern psikolojiye paralel yeni bir mânevî psikoloji geleneği oluşmaya başlamıştır. Modern psikolojinin metodu gereği benlik gelişimi algısı daha çok fizyo-psikolojiktir ve bu bakış tarzı insanın ruhsal/mânevî boyutunu ihmal etmektedir. Buna karşın sûfî geleneğin İslam inancı gereği benlik gelişimi modeli psiko-ruhsaldır ve buna göre insan beninin mânevî gelişimi söz konusudur. Biz de bu tebliğimizde Cemal Halvetî’nin insan beni ve mânevî gelişiminin yedi aşamasıyla ilgili ortaya koyduğu düşünceleri ele alıp günümüzde gelişmekte olan sûfî psikolojisine sağlayacağı katkıyı ortaya koymaya çalışacağız.